CD133 is indicative for a resistance phenotype but does not represent a prognostic marker for survival of non-small cell lung cancer patients - Salnikov, Alexey V.; Gladkich, Jury; Moldenhauer, Gerhard; Volm, Manfred; Mattern, Jürgen; Herr, Ingrid (International journal of cancer, 2010)
Despite advances in anticancer treatment, lung cancer still has poor prognosis. Recently, a cancer stem cell (CSC) hypothesis has emerged describing a small subset of tumor cells with stem cell properties. CSCs found in many solid tumors express CD133 antigen on the cell surface. The presence of CSC is correlated with poor survival of patients with glioblastomas, colon or prostate cancers. In this study, we evaluated whether CD133 expression in non-small cell lung cancer (NSCLC) has a prognostic value in patients' survival. We also analyzed whether CD133 positivity of NSCLC correlates with the expression of resistance-related proteins, angiogenic factors, oncogenes, proliferative activity or apoptosis. CD133 expression was retrospectively examined in a total of 88 cases of previously untreated NSCLC by immunohistochemistry. We found no correlation between CD133 positivity or the amount of CD133+ cells with NSCLC patients' survival, expression of oncogenes c-myc, c-N-ras, c-jun, c-fos, c-erbB1, c-erbB2 or p53, angiogenic factors VEGF, VEGFR-1, FGF, FGFR-1, tissue factor and with proliferative activity or apoptosis in NSCLC tissues. However, there was a significant association between the expression of resistance-related proteins glutathione S-transferase, thymidylate synthase, catalase, O6-methylguanine-DNA methyltransferase and p170 and CD133. Because CD133 expression is linked to a resistant phenotype, detection of CD133+ cells may be useful to predict efficacy of cytotoxic therapy but CD133 is not a strong prognostic parameter for survival of patients with NSCLC.
Erstmals am 12 Aug 2009 online veröffentlicht
Gesehen am 30.06.2023